ANALISIS KEJUTAN KEBIJAKAN FISKAL TERHADAP NILAI TUKAR RIIL DI INDONESIA: 1997 (III) â 2013 (IV) - , RHAHMADINI ISMET ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The aim of this study is to analyze the effects of fiscal shock on the real exchange rate in Indonesia for period of 1997.3 â 2013.4. This period is chosen because since August, 14th 1997 Indonesia has adopted free floating exchange rate regime. The variables that use in this study are national output (variable RGDP as a proxy variable), the real interest rate, trade openness that counted from volume of export and import relative to gross domestic bruto, and real government spending Indonesia. Augmented Distributed Lag-Insukindro Error Correction Model (ARDL I-ECM) is applied in this study. The usage of ARDL method because integration level and unit root test show that each variable has a different integration level, moreover, cointegration test result shows that there is long run relationship on model. Researcher applies ARDL I-ECM to estimate the effects of government spending shock on real exchange rate. The estimation results show that government spending shock have a positive impact on real exchange rate in short run. The value of fiscal shock coefficient in long run is near to zero (not significant). Those results indicate that fiscal shock has influence on real exchange rate in short run.